THE USE OF VAPOR RECOVERY UNIT (VRU) TO COVER EVAPORATON LOSS OH CONDENSATE TANK Y AND Z AT PT SHI PRABUMULIH - Sefilra Andalucia; Hendra Budiman; Irham Darmawan (Jurnal Cakrawala Ilmiah, 2023)
Crude oil is a mixture of hydrocarbon and non hydrocarbon in liquidp phase on earth. crude oil is not ready to use fuel or any other engery source. it needs to be processed through refining unit to be fuel. In the prosess of receving stockpiling and distribution of oil quantity loss can occur called losses. One of them is evaporation loss caused by evaporation that triggers of product loss. Fluid tend to evaporate according to its vapor pressure. The amount of evaporation loss occurred in condensate tank of Y and Z at PPP of PT SHI was rather high. The evaporation loss on tank type fixed cone roof tank was divided into breathing loss and working loss. Breathing loss refersh depreciation at night because of the environment temperatur. Meanwhile, working loss refers to losses of condensate product from liquid level change caused by receiving and distribusting activities. In this research, the author analyzed a new innovation to avoid evaporation loss on crude oi tank of condensate type using an effective and economic method. The company could apply vapor recovery unit using activated carbon system on condensate tank Y and Z. The economic research indicated that the profit was IDR 2.3 Billion and the investment cost was IDR 720.7 Million.